Severity of Dental Abrasion and Its Association with Oral Hygiene Behaviors: Severity of Dental Abrasion - Parveen, Saba; Hussain Chachar, Zaheer; Batool, Rida; Khalid, Qasim; Ejaz, Samia; Kumar, Rajesh (Pakistan Journal of Health Sciences, 2023)
Dental abrasion (DA) is an erosive activity that wears away the surface of teeth. Due to the use of abrasive dentifrices and incorrect brushing techniques, it is a multifactorial phenomenon. Objective: To assess the severity of dental abrasion in association with oral hygiene behaviors. Methods: A total of 278 undergraduate students aged 18 to 25 years were enrolled in this study who were having abrasion of permanent dentitions. Mouth mirror and CPITN probe were used to detect abrasion on the labial surface of front teeth and conducted a questionnaire. The Smith and Knight's Tooth Wear Index was used to measure the severity and frequency of dental abrasion in the patients. SPSS version-22 was used to analyze the data. Results: From 278 participants, females were 163 (58.6%) and males were 115 (41.4%). Majority 132 (47.5%) were using medium type of brush, most of the cases 122 (43.9%) brushing twice a day. About 107 (38.5%) using brushing methods in combination, 137 (49.3%) were using brush for 1-2 minutes. Tooth sensitivity was reported in 133 (47.8%) of the cases. Out of all, DA was found in 160 (58%) of the cases. According to severity, minimum loss of surface characteristics was in 220 (79.1%). A highly significant association (p=<0.001) was found between the type of brush and dental abrasion. A non-significant association (p=0.816) was found between both frequencies of brushing and dental abrasion. Conclusions: Brushing parameters did not affect abrasive lesions. Further study and long-term follow-up are required to distinguish oral hygiene routines from tooth abrasion